Agroecological tourism: bridging conservation, food security and tourism goals to enhance smallholders' livelihoods on South Pentecost, Vanuatu. Issue 8 (3rd August 2017) - Addinsall, Cherise; Weiler, Betty; Scherrer, Pascal; Glencross, Kevin
ABSTRACT: Smallholder farmers continue to make up the largest proportion of the world's disadvantaged. Rural smallholders in the South Pacific are particularly vulnerable to climate change, underinvestment and growing competition for land and resources. Strengthening synergies between agriculture and tourism through avenues such as agritourism has been widely discussed; however, very little research has approached these concepts from a sustainability perspective. This case study of rural Ni-Vanuatu smallholders uses the Agroecology and Sustainable Rural Livelihoods Framework (ASRLF) to explore tourism's potential contribution to improved conservation and food security outcomes. Data collection combined participatory methods such as "storian sessions" with analysis of secondary data. The findings highlight minimal current opportunities for rural Ni-Vanuatu smallholders to gain significantly from the tourism sector in Vanuatu. The shift from traditional gardening systems to cash cropping monocultures is also conflicting with tourism and conservation goals. This paper puts forward agroecological tourism as a strategy for integrating positive conservation, food security and livelihood outcomes for rural smallholders. It defines agroecological tourism as having a primary focus on the interpretation of sustainable traditional agroecosystems which exhibit cultural and heritage significance. Agroecological tourism has potential to support traditional practices, enhance the preservation of cultural knowledge and promote sustainable farming practices.